2005
DOI: 10.3988/jcn.2005.1.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Embolic Infarction Associated with Cardiac Amyloidosis

Abstract: Embolic cerebral infarction due to cardiac amyloidosis is rare. We report two patients with amyloidosis who developed cerebral infarcts. These embolic infarcts were probably related to cardiac involvement of amyloidosis, which was based on results of myocardial biopsy (Patient 1), and kidney biopsy and characteristic echocardiographic features including granular sparkling, restrictive cardiomyopathy and the presence of mural thrombus (Patient 2). Diffuse amyloid infiltration of the heart may have lead to impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…However, 4 of whose (including our case) medical history and electrocardiogram showing no evidence of atrial fibrillation, revealed intra-cardiac thrombus ( 13 , 15 , 16 ). 2 patients were proved by TEE ( 13 , 16 ), 1 by autopsy ( 16 ), and the other was not elaborated. As to the present case, he was found to have intra-cardiac thrombus by both TEE and CMR.…”
Section: Case Reportmentioning
confidence: 66%
See 3 more Smart Citations
“…However, 4 of whose (including our case) medical history and electrocardiogram showing no evidence of atrial fibrillation, revealed intra-cardiac thrombus ( 13 , 15 , 16 ). 2 patients were proved by TEE ( 13 , 16 ), 1 by autopsy ( 16 ), and the other was not elaborated. As to the present case, he was found to have intra-cardiac thrombus by both TEE and CMR.…”
Section: Case Reportmentioning
confidence: 66%
“…Prognosis of CA is generally poor. For patients with AL amyloidosis, the median survival is 6 months after appearance of congestive heart failure ( 13 , 23 ), however, patients with senile systemic amyloidosis and heart failure live with longer survival of 5 years ( 24 ). Cardiac troponins and NT-proBNP are important prognostic indicators in CA, and also allow for monitoring progression of disease or efficacy of therapy ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Immunoglobulin amyloid light chain amyloidosis may occur as a primary disease or in association with multiple myeloma or other plasma cell dyscrasia [1]. The heart is affected in over 50% of cases [2] but cerebral embolism in relation to cardiac amyloidosis has rarely been reported [1,3]. Herein, we report a patient with multiple myeloma who suffered from embolic infarction associated with cardiac amyloidosis diagnosed based on the kidney biopsy, echocardiographic and cardiac magnetic resonance imaging (MRI) results.…”
Section: Introductionmentioning
confidence: 97%